The place and the role of St. Cyril and St. Methodius in Slavic understanding and acceptance of the Christian ethical values - Donev, Dejan (Faculty of Philosophy, Skopje, 2019)
Мost of the moral philosophers are teachers, educators, saints of the illuminating word and deeds. Among them, two names do accentuate, the first one is Saint Cyril of Thessalonica (also known as Constantine the Philosopher) and the second one is Saint Methodius. They were not simply teachers of the illiterate, but they have sought to advance people - on those who have been on the edge of civilization to reveal the secrets of the spirit and mind, to help maladapted to get trained, the ignorant to be enable to be literate and to learn the secrets of life. That what true teachers are – enlighteners, and the wise thank them for these divine benefits.
Местото и улогата на св. Кирил и св. Методиј во словенското разбирање и прифаќање на христијанските етички вредности
Keywords: ethics, evil, god, education